Relationships between Body Mass Index and Social Support, Physical Activity, and Eating Habits in African American University Students - Wi-Young So, PhD; B. Swearingin, PhD; J. Robbins, PhD; P. Lynch, PhD; M. Ahmedna, PhD (Elsevier, 2012)
Purpose: We aimed to examine the relationships between obesity and the level of social support for healthy behaviors, amount of physical activity (PA), and dietary habits in African Americans. Methods: The subjects were 412 university students who visited a health promotion center at North Carolina A&T State University, Greensboro, NC, USA between September 1, 2009 and April 30, 2010. We administered a social support survey, the National Institutes of Health Fruit, Vegetable, and Fat Screener, the Paffenbarger PA Questionnaire, and measures of body mass index, waist circumference (WC), and blood pressure. Data were analyzed using a one-way analysis of variance and logistic regression analyses. Results: Results showed that men in the overweight group had WC and systolic blood pressure (SBP) measurements associated with increased risk of cardiovascular disease (CVD) and below average PA; those in the obese group had WC, SBP, and diastolic blood pressure (DBP) measurements associated with CVD risk and below average PA. Women in the overweight group had WC and SBP measurements associated with CVD risk, and those in the obesity group had WC, SBP, and DBP measurements associated with CVD risk and below average PA. Logistic regression analysis showed that increasing PA by 1,000 kcal/week decreased the prevalence of obesity by 9.3% in men and 9.0% in women. Conclusion: Thus, low PA was a significant risk factor for obesity among African Americans. However, the level of social support and consumption of fruits, vegetables, and fat were not found to be significant risk factors in this study.